A new ultrasound‐guided pubic approach for proximal obturator nerve block: clinical study and cadaver evaluation. (1st December 2015) - Yoshida, T.; Onishi, T.; Furutani, K.; Baba, H.
Summary: We evaluated an alternative technique for ultrasound‐guided proximal level obturator nerve block that might facilitate needle visualisation using in‐plane ultrasound guidance. Twenty patients undergoing transurethral bladder tumour resection requiring an obturator nerve block were enrolled into a prospective observational study. With the patient in the lithotomy position, the transducer was placed on the medial thigh along the extended line of the inguinal crease, and aimed cephalad to view a thick fascia between the pectineus and obturator externus muscles that contains the obturator nerve. A stimulating nerve block needle was inserted at the pubic region and advanced in‐plane with the transducer in an anterior‐to‐posterior direction. Eight ml levobupivacaine 0.75% was injected within the fascia. The median (IQR [range]) duration for ultrasound identification of the target and injection were 8.5 (7–12 [5–24]) s and 62 (44.5–78.25 [39–383]) s, respectively. All blocks were successful. A cadaver evaluation demonstrated that the dye injected into the target fascia using our technique travelled retrogradely through the obturator canal, and surrounded the anterior and posterior branches of the obturator nerve both proximally and distally to the obturator canal. We believe that this is a promising new technique for ultrasound‐guided proximal level obturator nerve block.